Asbabun Nuzul Ayat 178 Surah Albaqarah dan Hubungan Nya Dengan Qisas Sebagai Balasan Kejahatan Yang Setimpal - Fika Maharani; Khairunisa Azzahra; Faris Naufal; Pausi Rahman; Rudhatul Rizka Hasanah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The asbāb al-nuzūl (circumstances of revelation) of verse 178 of Surah Al-Baqarah is closely related to the establishment of divine legal principles concerning qiṣāṣ (retaliatory justice) and diyah (blood money). During the period of Jāhiliyyah (pre-Islamic Arabia), inter-tribal conflicts were common and often marked by cycles of violence and revenge that lacked clear legal or moral boundaries. In many cases, tribes would kill women or slaves and remain dissatisfied until they could retaliate further by killing a free person, whom they considered of higher social status, as compensation for the original loss. The revelation of Surah Al-Baqarah verse 178 addressed these unjust practices by introducing a principle of proportional and equitable justice. The verse stipulates that qiṣāṣ must be carried out fairly—“a free person for a free person, a slave for a slave, and a woman for a woman”—thereby eliminating arbitrary revenge and preventing the escalation of violence. This ruling rejected the Jahiliyyah notion that social hierarchy justified excessive retaliation and instead affirmed equality before the law. Moreover, the verse emphasizes that qiṣāṣ serves as a means of upholding justice through proportional punishment—life for life—while simultaneously offering a path toward mercy and reconciliation. It allows the victim’s family to forgive the offender in exchange for diyah, which must be given and received in a fair and respectful manner. Ultimately, the objective of this divine legislation is to promote taqwā (piety), restrain hostility, and bring an end to cycles of enmity and bloodshed within society.